Students’ Responses toward the Use of Interactive Dialogue Techniques in Speaking Class - -, Chairunnissa; Fahada, Nazli (English Language Teaching Prima Journal (ELT), 2025)
This research paper investigates students' responses to the implementation of interactive dialogue techniques in speaking classes, aiming to enhance their English speaking skills. Recognizing the challenges faced by learners, such as anxiety and lack of confidence, the study emphasizes the need for innovative, interactive teaching methods that foster meaningful communication. Utilizing a qualitative approach, data were collected through semi-structured interviews, classroom observations, and documentation at MTs Muhammadiya 15 Medan. Findings reveal that students experienced increased confidence, improved speaking fluency, and greater classroom engagement when engaging in dialogue-based activities. However, challenges such as limited vocabulary and difficulties with spontaneous speaking were also noted, highlighting the necessity for scaffolding strategies to support language acquisition. The study concludes that while interactive dialogue techniques positively impact students' speaking abilities, effective implementation requires targeted support to overcome inherent challenges, ultimately contributing to more dynamic and student-centered language instruction.